(untitled) (Heritage, 2020)
Domestic legal entity or entrepreneur, before issuing a licence, cannot begin carrying out an energy activity. A license is a legal act, which gives a certain right to a licence applicant. If an applicant has fulfilled all the conditions prescribed by law, in this case the competent authority shall take a decision which approves the application and issuing the license to carry out an energy activity. Otherwise, the request will be rejected or denied, depending on whether the applicant submitted all the necessary documentation or not. In the first case, upon examination of the documents submitted, it is found that this documentation could not be accepted as a relevant evidence. In the second case, the applicant did not submit all the necessary documentation within the prescribed period.